2017
DOI: 10.3233/thc-171311
|View full text |Cite
|
Sign up to set email alerts
|

Reflex-mediated dynamic neuromuscular stabilization in stroke patients: EMG processing and ultrasound imaging

Abstract: Abstract. BACKGROUND:Postural core instability is associated with poor dynamic balance and a high risk of serious falls. Both neurodevelopmental treatment (NDT) and dynamic neuromuscular stabilization (DNS) core stabilization exercises have been used to improve core stability, but the outcomes of these treatments remain unclear. OBJECTIVE: This study was undertaken to examine the therapeutic effects of NDT and DNS core stabilization exercises on muscular activity, core stability, and core muscle thickness. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…In fact, a recent clinical study demonstrated a superior effect of DNS on core muscle activation over the conventional NDT in sub-acute stroke patients. Specifically, transverse abdominal and internal oblique muscles electromyographic activity was significantly greater in the DNS group than the NDT group, supporting the notion that the subconscious core stabilization method is more beneficial for deep core muscle activity control [11].…”
Section: Introductionsupporting
confidence: 56%
“…In fact, a recent clinical study demonstrated a superior effect of DNS on core muscle activation over the conventional NDT in sub-acute stroke patients. Specifically, transverse abdominal and internal oblique muscles electromyographic activity was significantly greater in the DNS group than the NDT group, supporting the notion that the subconscious core stabilization method is more beneficial for deep core muscle activity control [11].…”
Section: Introductionsupporting
confidence: 56%
“…DNS can also be used to improve neck muscles coordination to treat cervical instability and neck pain (Cha et al, 2018). Furthermore, DNS methods were found to be effective in the rehabilitation of balance, gait, stance and core stabilization in neurological disorders such as cerebral palsy Son et al, 2017) or stroke (Yoon and You, 2017).…”
Section: Dynamic Neuromuscular Stabilizationmentioning
confidence: 99%
“…DNS manual treatment makes use of specific functional exercises to improve spinal and joint stability by focusing on the integrated stabilization system (Frank et al, 2013). Although statistical reliability of the DNS tests is limited good effect of DNS therapeutic procedures (Cha et al, 2018;Davidek et al, 2018;Juehring and Barber, 2011;Kim et al, 2017;Kobesova et al, 2018Kobesova et al, , 2015Oppelt et al, 2014;Son et al, 2017;Yoon and You, 2017) suggests clinical utility of the DNS tests since the therapy, training and individual correction of the clients in the studies listed above was always based on DNS functional tests. A study exploring reliability of individual DNS tests has been in process.…”
Section: Dynamic Neuromuscular Stabilizationmentioning
confidence: 99%
“…The abdominal expansion (AE) strategy has been increasingly used by a therapeutic approach, dynamic neuromuscular stabilization, prior to purposeful movement during daily activities, and as the essential foundation of their stabilization exercises [ 13 , 14 , 15 ]. In contrast to the AD strategy, the AE strategy involves eccentric contraction of the abdominal muscles accompanied by downward contraction of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%